Optimization of Environmentally Benign Polymers Based on Thymine and Polyvinyl Sulfonate Using Plackett-Burman Design and Surface Response - Julieta Ledesma; Santiago A. Bortolato; Carlos E. Boschetti; Débora M. Martino (Journal of Chemistry)
Traditional approaches to the development of integrated circuits involve the use and/or manufacture of toxic materials that have a potential environmental impact. An extensive research has been done to design environmentally benign synthetic polymers containing nucleic acid bases, which can be used to enhance the photoresistor technologies. Water soluble, environmentally benign photopolymers of 1-(4-vinylbenzyl) thymine (VBT) and vinylphenyl sufonate (VPS) undergo a photodimerization reaction when exposed to low levels of ultraviolet irradiation leading to an immobilization of the copolymer on a variety of substrates. Plackett-Burman design (PBD) and central composite design (CCD) were applied to identify the significant factors influencing the polymer crosslinking and dye adsorption processes, which are relevant in the fabrication of copolymer films for potential photoresist use. The PBD results assigned a maximum absorption signal of 0.67, while optimal conditions obtained in this experiment following the CCD method predictions provided a response of 0.83 ± 0.03, being a solid foundation for further use of this methodology in the production of potential photoresistors. The pH effect was relevant for low concentrations but not significant for higher concentrations. To the best of our knowledge, this was the first report applying statistical experimental designs to optimize the crosslinking of thymine-based polymers.